Secagem de sementes de soja em secador rotoaerado: modelagem do processo e análise da qualidade das sementes - Avendaño, Pablo de Souza (2020)
Soy is a crop that has been used in human food for over five thousand years. Its grain is among the most consumed in the world because it is an excellent source of protein and vegetable oil to meet human and animal food requirements. Until the 2018 and 2019 harvests, Brazil ranked second in the world in soybean production, but due to the drop in production in the United States and the strong growth in Brazilian production, in the 2019/20 harvest, Brazil reached the first place with highlights in productivity. Maintaining the quality of soybean seeds is essential to meet the demands all year round. Drying is one of the most critical operations and requires greater management, since the viability of the seeds can be reduced considerably by delaying or poorly executing the operation. Therefore, this work aimed to study the drying process of soya beans in a non-conventional rotary dryer, called rotoaerated, to evaluate the heat and mass transfer process in this system, as well as to analyze the influence of process variables on the quality of these seeds. It was possible to determine the humidity of the solids along with the dryer, the final temperature and quality of the seeds, as well as the temperature and speed of the drying air in each test. The rotoaerated dryer showed excellent results regarding the drying rate (0.051 to 0.113ppmin-1) when compared to others, besides a low residence time (between 22.2 and 24.9min), providing final moisture values for the seed suitable for storage. The computer simulations were performed using the two-phase model and showed good agreement with the experimental values. The average deviations were 1.08, 5.7, and 10.9% for the final moisture and final temperature of the soybean seeds and input air temperature, respectively. The effects of the process variables on seed quality were quantified and provided quality indexes above 90%, and the drying air temperature can reach 50°C, however, for this temperature the input air velocity should be the lowest possible (1.6 ms-1).